2006
DOI: 10.1196/annals.1386.047
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and the Estrogen Receptor

Abstract: :  The position effect variegation in Drosophila and Schizosaccharomyces pombe, and higher‐order chromatin structure regulation in yeast, is orchestrated by modifier genes of the Su(var) group, (e.g., histone deacetylases ([HDACs]), protein phosphatases) and enhancer E(Var) group (e.g., ATP [adenosine 5′‐triphosphate]‐dependent nucleosome remodeling proteins). Higher‐order chromatin structure is regulated in part by covalent modification of the N‐terminal histone tails of chromatin, and histone tails in turn s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 52 publications
(119 reference statements)
0
25
0
Order By: Relevance
“…The expression of ERs is inhibited by reversible methylation and acetylation of histones at the promoter (Leader et al 2006). Da Silva Faria et al (2008 reported morphological changes ("regression") in the ovaries, increased E 2 serum concentrations, and decreased mRNA expression of ovarian receptors ERα, ERβ1, and ERβ2 in the female offspring of rats suffering from protein-energy malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ERs is inhibited by reversible methylation and acetylation of histones at the promoter (Leader et al 2006). Da Silva Faria et al (2008 reported morphological changes ("regression") in the ovaries, increased E 2 serum concentrations, and decreased mRNA expression of ovarian receptors ERα, ERβ1, and ERβ2 in the female offspring of rats suffering from protein-energy malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has focused on mechanisms that regulate ERα expression in human breast cancer cells. Epigenetic mechanisms including DNA methylation and/or histone modifications are believed to contribute to silencing of ERα expression [129,130]. Several studies have demonstrated that ERα CpG islands are hypermethylated in ERα-negative human breast cancer cells and treatment of these cells with DNA methyltransferase inhibitors such as 5-azacitidine or decitabine elicits reexpression of functional ERα protein (Fig.…”
Section: Epigenetic Regulation Of Estrogen Receptor Expressionmentioning
confidence: 99%
“…In addition, ERa appears to be directly acetylated by p300, which leads to a decrease in its transactivation activity. 23 Intriguingly, one of the lysines acetylated by p300, K303, is frequently mutated in early breast cancer lesions, 24 providing a direct link between HAT function and cancer development. Furthermore, mutation of K303 and subsequent ectopic expression of the mutated protein causes faster growth of cultured breast carcinoma cells.…”
Section: Era and Hatsmentioning
confidence: 99%